Literature and the child : romantic continuations, postmodern contestations - McGavran, James Holt, Jr., 1941-2014 (Iowa City : University of Iowa Press, 1999)
These distinguished essays powerfully define the myriad ways in which the Romantic image of the child, so compellingly portrayed by Wordsworth and Blake, continues to haunt us, shaping contemporary visions of childhood from Calvin and Hobbes to postmodernist poetry and fiction to sociological discussions of child-labor, child-abuse and the feminization of poverty. Literature and the Child, ably edited by James Holt McGavran, should be read by anyone interested in the history of the cultural construction of childhood.--Anne K. Mellor.
Romantic Continuations, Postmodern Contestations, or, "It's a Magical World, Hobbes, Ol' Buddy" ... Crash! / James Holt McGavran -- Romanticism Continuing and Contested -- Romanticism and the End of Childhood / Alan Richardson -- Reading Children and Homeopathic Romanticism: Paradigm Lost, Revisionary Gleam, or "Plus Ca Change, Plus C'est la Meme Chose"? / Mitzi Myers -- Romantic Ironies, Postmodern Texts -- Taking Games Seriously: Romantic Irony in Modern Fantasy for Children of All Ages / Dieter Petzold -- "Infant Sight": Romanticism, Childhood, and Postmodern Poetry / Richard Flynn -- Wordsworth, Lost Boys, and Romantic Hom(e)ophobia / James Holt McGavran -- Romanticism and the Commerce of Children's Books -- Sensational Designs: The Cultural Work of Kate Greenaway / Anne Lundin -- The Marketing of Romantic Childhood: Milne, Disney, and a Very Popular Stuffed Bear / Paula T. Connolly -- Romantic Ideas in Cultural Confrontations -- The Art of Maternal Nurture in Mary Austin's The Basket Woman / William J. Scheick -- Romanticism and Archetypes in Ruth Nichols's Song of the Pearl / Teya Rosenberg.
Includes bibliographical references and index.
Print version record.
eBooks on EBSCOhost
Keywords: Children's literature, English -- History and criticism; Children's literature, American -- History and criticism; Children -- Books and reading; Postmodernism (Literature); Romanticism; Littérature de jeunesse anglaise -- Histoire et critique; Littérature de jeunesse américaine -- Histoire et critique; Enfants -- Livres et lecture; Postmodernisme (Littérature); Romantisme; romanticism (form of expression); LITERARY CRITICISM -- European -- English, Irish, Scottish, Welsh; SOCIAL SCIENCE -- Children's Studies; Children -- Books and reading; Children's literature, American; Children's literature, English; Postmodernism (Literature); Romanticism; Das Romantische; Jugendliteratur; Englisch; Criticism, interpretation, etc